Kontribusi Pengelolaan Agroforestry Terhadap Pendapatan Petani (Studi Kasus Desa Ranaka Kecamatan Wae Ri’i Kabupaten Manggarai) - Florentina Jebaru; Wilhelmina Seran; Nixon Rammang (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
This research was conducted to determine the contribution of agroforestry to farmers' income. This research was conducted in Ranaka village, WaeRi'i sub-district, Manggarai Regency